1980
DOI: 10.1271/bbb1961.44.1535
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of fragrant materials. IV. A new keto-alcohol, (-)-mintlactone, (+)-isomintlactone and minor components in peppermint oil.

Abstract: Eighty-one constituents were newly identified from the oil of Mentha piperita L ., including a new keto-alcohol, (-)-mintlactone and (+)-isomintlactone. They were determined by spectral data and syntheses to be 4-hydroxy-4-methyl-2-cyclohexen-lone (8), (6R, 7aR) (10) and (6R, 7aS)-3,6-dimethyl-5,6,7,7a-tetrahydro-2(4H)-benzofuranone (11) , respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 2 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…One of the possible synthetic applications of these ethers could be the construction of α,β-unsaturated lactones, an important class of natural products. For example, the cyclic ether 1a could be transformed into isomintlactone, through dehydration followed by allylic oxidation . Nevertheless, the hydroxyl group of 1a proved to be very resistant to several dehydration conditions.…”
mentioning
confidence: 99%
“…One of the possible synthetic applications of these ethers could be the construction of α,β-unsaturated lactones, an important class of natural products. For example, the cyclic ether 1a could be transformed into isomintlactone, through dehydration followed by allylic oxidation . Nevertheless, the hydroxyl group of 1a proved to be very resistant to several dehydration conditions.…”
mentioning
confidence: 99%
“…Many minor components were detected, including the menthol isomers isomenthol ( 5 ) and neomenthol ( 6 ). The menthol concentration for the oil used in this study was rather higher than in some previously reported GC−MS analyses of peppermint oils from different sources. The ES−MS of the crude derivatized peppermint oil, shown in Figure a, indicated ions at m / z 383, the molecular ion of derivatized menthol, but in this case the reaction byproduct at m / z 428 was the base peak in the spectrum. In addition, there were numerous peaks of much less abundance in the spectrum that could not be assigned with certainty.…”
Section: Resultsmentioning
confidence: 57%
“…and neomenthol [5]. The menthol concentration for the oil used in this study was higher than in some previously reported GC/EI-MS analyses of peppermint oils from different sources (11,19,20). Derivatives of the known alcohols in peppermint oil each fragmenttoformtheproductionatmlz llO.Thus, t h e d z 110 precursor scan in Figure 5 shows as the base peak mlz 248 for derivatized menthol and its isomers.…”
Section: Es-ms/ms Analyses Of Each Oil Is Discussed In Turnmentioning
confidence: 67%